Predictors of COVID-19 Vaccine Hesitancy in North-Central Nigeria - Olutola, Ayodotun; Bola Gobir, Ibrahim; Bazira, Deus; Agboola, Samson; Ohunene Sanni, Fatimah; Akanbi Bello, Azeez; Onyinyechi Havila, Nnadozie; Adamu, Aisha; Bello, Fatima; Angmun Otubo, Suzzy; Piring'ar Nyang, Mercy (Journal of Immunization, 2024)
COVID-19 vaccine hesitancy has emerged as a major challenge to global efforts to control the pandemic, particularly in Nigeria, where hesitancy to other effective vaccines such as polio and measles has been widely reported. Several individual, societal, and structural factors contribute to this behaviour and prevent the effectiveness of COVID-19 prevention efforts. Objectives This study sought to identify the predictors of COVID-19 vaccine hesitancy in the seven states of North-Central, Nigeria. Methods A population-based cross-sectional online survey was conducted among residents using a semi-structured questionnaire adapted from the WHO SAGE vaccine hesitancy scale and distributed via social media networks over 8-weeks. Results A total of 1,429 responses met the inclusion criteria and were analysed. Among the respondents, 60.7% were males, 47.5% were between the ages of 26 and 45, and 80.1% had postsecondary education. A total of 421 respondents (29.5%) were hesitant and unwilling to receive the vaccine. The reasons for hesitancy were concerns about side effects (37.1%), doubt about the existence of COVID-19 (11.0%), and the perception of time required to receive the vaccine (9.6%). Post-secondary education (AOR: 0.49, 0.36-0.66) and people of the Islamic faith (AOR: 0.68, 0.52-0.90) were found to be associated with lower levels of hesitancy. Conclusion The study found that vaccine hesitancy is a complex problem that is linked with multiple social determinants of health as lower educational attainment, lower income and Christian faith were found to be predictors of vaccine hesitancy. Confidence, Complacency and Convenience factors were expressed by respondents as concerns about side effects, doubt about the existence of COVID-19 and time required to receive the vaccines were the most prominent reasons for unwillingness to receive the vaccine. In order to protect the public health of communities, targeted interventions are required to increase vaccine acceptance by cultivating trust in vaccines, disseminating accurate information, and engaging with community stakeholders including religious groups.
Keywords: COVID-19; vaccination rates; vaccine hesitancy; vaccine acceptance; socioeconomic.